The Analysis Of Multiple-Choice Test Quality For Reading III Class In English Education Department, Universitas Pendidikan Ganesha Bali, Indonesia - Paramartha, A.A. Gede Yudha (Journal of Education Reseach and Evaluation, 2017)
This study aimed at investigating the quality of 40-item multiple-choice taken from Reading III class in English Education Department. It was carried out in order to get clearer picture and provide feedbacks on how the Critical Reading test for the new curriculum should be developed and what factors should be taken into account when developing the test. The data were taken from 24 fourth semester students in English Education Department, Unidksha, Bali who took the reading test. The data were analyzed by conducting Classical Test Theory analysis with the assistance of jMetrik software. In general, the result shows that the test was consistent but it was easy and only 40% of total items are eligible to be used. Along the findings and discussion, some feedbacks are provided for future development for the reading test.